Profile of infective microorganisms causing ventilator-associated pneumonia: A clinical study from resource limited intensive care unit - Bhaskar Thakuria; Preetinder Singh; Sanjay Agrawal; Veena Asthana (Wolters Kluwer Medknow Publications, 2013)
Background: Ventilator-associated pneumonia (VAP) is the most common cause of hospital acquired infection and death among patients admitted in ICU. Microorganisms responsible for VAP vary from place to place. Gram-negative bacteria (GNB) have emerged as a major group of pathogen causing VAP and over the years carbapenem group of antibiotics has emerged as one of the important antibiotics used in the critically ill patients. There have been reports of increased occurrence of infection by carbapenem-resistant bacteria in health care settings in recent times. Aim: The aim of the study was to assess the incidence of VAP, their microbiological profile with reference to carbapenemase producing GNB in the intensive care unit of a tertiary care hospital, their relation to initial emperical antibiotic therapy, sensitivity patterns, and outcome. Materials and Methods: This prospective study was carried out over the period of 1 year (July 2010-June 2011) on 100 randomly selected patients above the age of 18 years admitted in the emergency/ICU and requiring intubation and mechanical ventilation for more than 72 hours. The diagnosis of VAP was established on the basis of clinical and radiological parameters as per Centre of Disease Centres (CDC) guidelines. A baseline sample was obtained after initial endotracheal intubation. Thereafter, the culture sent on the first day of occurrence of clinical sign of VAP. Culture was done on blood agar and MacConkey agar. All imipenem-resistant strains were further confirmed by Modified Hodge test and combined disc for confirmation of respective carbapenemase. Results: Incidence of VAP was found to be 51%. GNB mainly Citrobacter 28 (52.83%) and Klebsiella pneumoniae 7 (13.21%), were the most commonly isolated pathogens. The prevalence of carbapenemase-producing GNB was alarmingly high 24/50 (48%). The entire carbapenemase producers showed high degree of cross resistance to antibiotics with some sensitivity to Polymyxin B (94 %) and Tigecycline (96%) Conclusion: High incidence of VAP and the potential carbapenemase-producing GNB are real threat in our ICU. The emergence of microorganisms known for its inherent resistance among most of the common first-line antibiotics calls for a alarm in all upcoming tertiary care hospitals.